2009
DOI: 10.1016/j.ejvs.2009.02.002
|View full text |Cite
|
Sign up to set email alerts
|

New Insight in Aetiopathogenesis of Aortic Diseases

Abstract: Aortic diseases are diverse, and involve a multiplicity of biological systems in the vascular wall and at the interface with blood. Future research needs to unravel distinct cellular and molecular mechanisms causing the clinical events, in particular, dissection, expansion of already formed aneurysms and rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 47 publications
2
74
0
2
Order By: Relevance
“…Pathomorphological studies have shown that DAA is characterized by aortic media thinning accompanied by smooth muscle vascular attenuation and extracellular matrix destruction determined by inflammation, oxidative stress and proteolysis, as well as by the formation of minor intramural thrombi inducing impaired endothelial integrity [30] [31]. Endothelial cells play a key role in maintained vascular integrity, inflammation and thrombosis control, as well as mural cells and matrix component.…”
Section: Discussionmentioning
confidence: 99%
“…Pathomorphological studies have shown that DAA is characterized by aortic media thinning accompanied by smooth muscle vascular attenuation and extracellular matrix destruction determined by inflammation, oxidative stress and proteolysis, as well as by the formation of minor intramural thrombi inducing impaired endothelial integrity [30] [31]. Endothelial cells play a key role in maintained vascular integrity, inflammation and thrombosis control, as well as mural cells and matrix component.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ascending TAAs are associated with an underlying bicuspid aortic valve (BAV) with an estimated 75 % of patients who underwent BAV replacement demonstrating cystic medial necrosis on biopsy, compared to 14 % in patients who had tricuspid valve replacement. Inadequate levels of firillin-1 may be responsible for this weakness in aortic wall leading to BAV (Huntington et al, 1997 Allaire, et al, 2009). …”
Section: Structural Considerations In Taamentioning
confidence: 99%
“…TIMP-2, a broad-spectrum MMP inhibitor, and PAI-1, an inhibitor of tPA and uPA, are less expressed in AAA walls than in AOD, suggesting that ECM destruction is caused by a decrease in inhibitors and an increase in proteases (Allaire et al, 2009). Alpha-1-antitrypsin and Alpha-2-macroglobulin may suppress elastolysis, which is responsible for 90% of the inhibition of circulating MMPs, (Cohen et al, 1990).…”
Section: Inhibition Of Mmpsmentioning
confidence: 99%
“…Abdominal aortic aneurysms (AAAs), for instance, are the 3 th leading cardiovascular cause of death (Sakalihasan et al, 2005;Allaire et al, 2009). The AAA represents a widening of the abdominal aorta generally caused by the hardening of the arteries known as the atherosclerosis.…”
Section: Abdominal Aortic Aneurysm (Aaa)mentioning
confidence: 99%
“…In order to validate concepts of an endovascular gene therapy developed in surgical research laboratory (Allaire et al, 2004;Dai et al, 2005;Allaire et al, 2009), the experimental xenograft model of AAA was used. First, the abdominal aorta of male guinea pigs was removed and decellularized with a detergent, 0.1% sodium dodecyl sulfate (SDS).…”
Section: Xenograft Modelmentioning
confidence: 99%